2023
DOI: 10.1037/pag0000742
|View full text |Cite
|
Sign up to set email alerts
|

Increased cognitive effort costs in healthy aging and preclinical Alzheimer’s disease.

Abstract: Life-long engagement in cognitively demanding activities may mitigate against declines in cognitive ability observed in healthy or pathological aging. However, the “mental costs” associated with completing cognitive tasks also increase with age and may be partly attributed to increases in preclinical levels of Alzheimer’s disease (AD) pathology, specifically amyloid. We test whether cognitive effort costs increase in a domain-general manner among older adults, and further, whether such age-related increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Our prior work suggests that the Cog-ED may be a particularly useful tool for investigating the neurobiological substrates underlying cognitive effort-based decision-making in both healthy aging and Alzheimer's disease (AD). We and others have found that both populations exhibit reduced motivation to engage in cognitive effort (Aschenbrenner et al, 2023;Crawford et al, 2023;Heron et al, 2018). The present study suggests the possibility that such effects might result from age-related changes in dACC functioning.…”
Section: Discussionsupporting
confidence: 63%
“…Our prior work suggests that the Cog-ED may be a particularly useful tool for investigating the neurobiological substrates underlying cognitive effort-based decision-making in both healthy aging and Alzheimer's disease (AD). We and others have found that both populations exhibit reduced motivation to engage in cognitive effort (Aschenbrenner et al, 2023;Crawford et al, 2023;Heron et al, 2018). The present study suggests the possibility that such effects might result from age-related changes in dACC functioning.…”
Section: Discussionsupporting
confidence: 63%
“…Even subclinical, relative weaknesses within these three subcomponents of executive function alone can result in individuals who will tend to show response patterns notable for being more concrete, impulsive, or distractable, all of which intuit different methods of management (e.g., coping skills training with strategy development, environmental modification, and use of reminder systems). With age-associated decrements in cognition, the ability to flexibly cope with new situations may be constrained as these skills become less efficient (Park and Reuter-Lorenz, 2009;Oberlin et al, 2016;Aschenbrenner et al, 2023), creating a potentially 'vicious cycle' by which worsening executive function leads to poorer behavioral regulation, which further degrades executive functioning resources (Morris et al, 2015;Grech et al, 2019).…”
Section: Age-related Differences In Self-regulatory Stylesmentioning
confidence: 99%
“…These values do not take into consideration comorbidities that may be present. Numerous studies outline the financial burden that AD places on patients and their families ( Aschenbrenner et al, 2023 ; Brockmann et al, 2023 ; Mahase, 2023 ).…”
Section: Introductionmentioning
confidence: 99%